2020
DOI: 10.1021/acs.est.0c01841
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Tracing of Anthropogenic Magnetite Nanoparticles in the Urban Atmosphere

Abstract: Nanosized magnetite is a highly toxic material due to its strong ability to generate reactive oxygen species in vivo, and the presence of magnetite NPs in the brain has been linked with aging and neurodegenerative diseases such as Alzheimer’s disease. Recently, magnetite pollution nanoparticles (NPs) were found to be present in the human brain, heart, and blood, which raises great concerns about the health risks of airborne magnetite NPs. Here, we report the abundant presence and chemical multifingerprints (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 65 publications
6
88
0
Order By: Relevance
“…The sample with the highest specific area was sample 7# (54.2 m 2 /g), while the lowest was sample 5# (16.8 m 2 /g). Zhang et al (2020b) found that magnetic iron oxides would enhance the toxicity effect because that it enhances the co-deposition of other ferromagnetic or paramagnetic substances and promotes the accumulation in the human body. The magnetization curves and saturation magnetization values of the particles are shown in Figure S6a and S6b.…”
Section: Particle Structure Analysismentioning
confidence: 99%
“…The sample with the highest specific area was sample 7# (54.2 m 2 /g), while the lowest was sample 5# (16.8 m 2 /g). Zhang et al (2020b) found that magnetic iron oxides would enhance the toxicity effect because that it enhances the co-deposition of other ferromagnetic or paramagnetic substances and promotes the accumulation in the human body. The magnetization curves and saturation magnetization values of the particles are shown in Figure S6a and S6b.…”
Section: Particle Structure Analysismentioning
confidence: 99%
“…Magnetite (Fe 3 O 4 ) is a kind of naturally occurring mineral, and it is also ubiquitous in the atmospheric environment. 1–6 Several studies have found that airborne magnetite nanoparticles were present in different human organs, suggesting that magnetite nanoparticles in the atmosphere may be able to enter the human circulatory system or even the brain tissue. 4,7,8…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a significant knowledge gap in understanding traffic-derived magnetite pollution. Magnetite particles in the atmosphere usually originate from various sources including coal combustion 1,19 and traffic emission. 1,3 Beyond that, some minor sources also contribute to the Fe-containing metal oxide particles in urban areas, including natural minerals, domestic sources ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The exogenic magnetite nanoparticles present a different morphology from the endogenic [7]. Significant concerns were raised for increased health risks as these nanoparticles are regarded as highly toxic [8]. They can enter the blood flow and be transported to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…They can enter the blood flow and be transported to the brain. Moreover, they can catalyze the generation of reactive oxygen species in vivo and cause protein modification, lipid peroxidation, or DNA damage [8]. The increased magnetite content in the human brain raises another question about its contribution to the mechanism of thermal or non-thermal interactions with electromagnetic fields in high frequencies.…”
Section: Introductionmentioning
confidence: 99%